2017
DOI: 10.1016/j.avsg.2017.06.043
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Multicenter Clinical Trial on the Safety and Efficacy of a Ready-to-Use Fibrin Sealant as an Adjunct to Hemostasis during Vascular Surgery

Abstract: FS Grifols was efficacious and safe as an adjunct to anastomotic hemostasis in patients undergoing arterial surgery using prosthetic material with mild to moderate bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…The final stage of the physiological coagulation cascade results in the production of thrombin, which converts fibrinogen to fibrin and eventually forms a semi‐rigid fibrin clot that blocks the bleeding port. Chetter et al found that fibrin Grifols has better hemostatic effect than manual pressurization and is safe and effective for patients with mild to moderate bleeding …”
Section: Hemostasis At Nanoscalementioning
confidence: 99%
“…The final stage of the physiological coagulation cascade results in the production of thrombin, which converts fibrinogen to fibrin and eventually forms a semi‐rigid fibrin clot that blocks the bleeding port. Chetter et al found that fibrin Grifols has better hemostatic effect than manual pressurization and is safe and effective for patients with mild to moderate bleeding …”
Section: Hemostasis At Nanoscalementioning
confidence: 99%
“…FS Grifols is a product composed of frozen solutions of highly purified human fibrinogen (80 mg/mL) and human thrombin (500 IU/mL) with calcium chloride (5.9 mg/mL) supplied as a ready-to-use kit, in pre-loaded glass syringes assembled on a syringe holder. 13 For the specific use on the surface of hepatic resections, FS Grifols was delivered using spray applicator tips [Gas Assisted Applicator Kit, 5 cm 3 . Micromedics, Inc. Eagan, MN, USA].…”
Section: Investigational Treatmentsmentioning
confidence: 99%
“…The primary efficacy endpoint of the study was the proportion of patients in both treatment groups who achieved hemostasis at the TBS by 4 min (T 4 ) following the T Start without occurrence of re-bleeding until the completion of the surgical closure. The 4-min time point was chosen based on efficacy results observed in previous studies with other FS products and previous data, 8,[13][14][15][16][17][18][19][20][21][22] as well as on the US FDA feedback provided to the sponsor in discussing the protocol design and its adequacy for the aim of supporting a marketing application in the claimed indication. Hemostasis was defined as a cessation of bleeding at the TBS.…”
Section: Efficacy Endpointsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biocompatibility of polytetrafluoroethylene and Dacron has been proved in many in vivo and clinical tests. [12][13][14][15][16][17] Apart from biologically stable materials (practically non-degraded in an organism), biodegradable materials are increasingly being used. The best known are: polylactic acid and its copolymers, poly-ε-caprolactone, poly(glycolic acid), alginates, or chitin derivatives.…”
Section: Introductionmentioning
confidence: 99%